2013
DOI: 10.5142/jgr.2013.37.269
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ginsenoside composition of ginseng berry extracts after a microwave and vinegar process

Abstract: MGB-20 findings show that the ginseng berry extracts that had been processed with microwave and vinegar for 20 min peaked in the level of ginsenoside Rg2 (2.28%) and Rh1 (1.28%). MGB-1 peaked in the level of ginsenoside Rg3 (1.13%) in the ginseng berry extract processed with microwave and vinegar for 1 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Many techniques involving their extraction, purification and analysis have been employed from a variety of host tissues such as roots (Lin et al 2013;Sunwoo et al 2014), leaves (Lee et al 2012) and even berries (Kim et al 2013). The preferred solvent under use involves methanol often in aqueous solutions, in conjunction with heat, refluxing or sonication-based extraction methodologies (Corbit et al 2005;Engelberth et al 2010).…”
mentioning
confidence: 99%
“…Many techniques involving their extraction, purification and analysis have been employed from a variety of host tissues such as roots (Lin et al 2013;Sunwoo et al 2014), leaves (Lee et al 2012) and even berries (Kim et al 2013). The preferred solvent under use involves methanol often in aqueous solutions, in conjunction with heat, refluxing or sonication-based extraction methodologies (Corbit et al 2005;Engelberth et al 2010).…”
mentioning
confidence: 99%
“…Methods of bioconversion by enzymes and endophytes have been developed to transform saponins to less polar ginsenosides [6], [7]. It was confirmed that it is possible to transform polar ginsenosides to less polar ginsenosides by a microwave and vinegar process [8]. However, transformation by heating in a reaction kettle is more conducive for application in a factory as compared to the other methods.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that organic acids such as acetic acid, ascorbic acid, citric acid, malic acid, lactic acid, and oxalic acid could convert neutral ginsenosides to rare ginsenosides, resulting in improved functionality of ginseng, hence increasing its value (Jang et al., 2018; Kim et al., 2010; Liu et al., 2016; Yi et al., 2010). After heat treatment, the major ginsenosides could be converted to low‐polar ginsenosides such as Rg2, Rg6, F4, Rk3, and Rg5 by hydrolysing the sugar chains (Kim et al., 2013; Zhang et al., 2012).…”
Section: Introductionmentioning
confidence: 99%